2015
DOI: 10.2140/agt.2015.15.3535
|View full text |Cite
|
Sign up to set email alerts
|

A generating set for the palindromic Torelli group

Abstract: A palindrome in a free group F n is a word on some fixed free basis of F n that reads the same backwards as forwards. The palindromic automorphism group ΠA n of the free group F n consists of automorphisms that take each member of some fixed free basis of F n to a palindrome; the group ΠA n has close connections with hyperelliptic mapping class groups, braid groups, congruence subgroups of GL(n, Z), and symmetric automorphisms of free groups. We obtain a generating set for the subgroup of ΠA n consisting of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Finally, in Section 6, we prove that P I n = IA n ∩ EΠA ′ n . This result strengthens a recent result of Fullarton [3].…”
Section: The Groupsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, in Section 6, we prove that P I n = IA n ∩ EΠA ′ n . This result strengthens a recent result of Fullarton [3].…”
Section: The Groupsupporting
confidence: 92%
“…Clearly, IA n ∩ EΠA ′ n ⊂ IA n ∩ ΠA n = P I n . In [3], Fullarton showed that P I n is normally generated in ΠA n by the automorphisms [µ 12 3 and hence they also lie in IA n ∩EΠA ′ n . Note that, IA n is a normal subgroup of Aut(F n ).…”
mentioning
confidence: 99%
“…On the other hand, Szepietowski [18] gave a finite generating set for Γ 2 (N g ), and then the first author and Sato [6] gave a minimal generating set for Γ 2 (N g ). Fullarton [4], the second author [8], Margalit and Putman gave a finite presentation for Γ 2 (n) independently. Therefore, we obtain a normal generating set for I(N g ) in Γ 2 (N g ).…”
Section: Figurementioning
confidence: 99%
“…In particular, he studied involutions and center of ΠA(F n ). In a recent paper [10], Fullarton obtained a generating set for the palindromic IA-automorphism group P I(F n ). This was obtained by constructing an action of P I(F n ) on a simplicial complex modelled on the complex of partial bases due to Day and Putman [7].…”
Section: Introductionmentioning
confidence: 99%
“…This was obtained by constructing an action of P I(F n ) on a simplicial complex modelled on the complex of partial bases due to Day and Putman [7]. The papers [11] and [10] indicates a deep connection between palindromic automorphisms of free groups and geometry. Recently, Bardakov, Gongopadhyay and Singh [3] investigated many algebraic properties of ΠA(F n ).…”
Section: Introductionmentioning
confidence: 99%